Lewis Morley - Morley, Lewis, 1925-2013.; Annear, Judy.; Humphries, Barry, 1934-2023.; Art Gallery of New South Wales (Sydney : Art Gallery of New South Wales, 2006)
Lewis Morley began his photographic career in London in the late 1950s working for Tatler, London Life and She. He took the first fashion photos of Twiggy and Jean Shrimpton and in 1963 took the iconic image of the naked Christine Keeler astride a chair. He has lived and worked in Australia since 1971.
Catalogue of an exhibition held at the Art Gallery of New South Wales, Sydney, 7th July - 10th September 2006.
Lewis Morley interviewed by Judy Annear. Essay by Barry Humphries.
Bibliography: p. 120.
Keywords: Morley, Lewis, -- 1925-2013 -- Exhibitions; Morley, Lewis, -- 1925-2013 -- Interviews; Photography, Artistic -- Exhibitions